From Light to Logic: Recent Advances in Optoelectronic Logic Gate - Woochul Kim; Dante Ahn; Minz Lee; Namsoo Lim; Hyeonghun Kim; Yusin Pak (Small Science)
This review delves into the advancements in optoelectronic logic gate (OELG) devices, emphasizing their transformative potential in computational technology through the integration of optical and electronic components. OELGs present significant advantages over traditional electronic logic gates, including enhanced processing speed, bandwidth, and energy efficiency. The evolution of OELG architectures from single‐device, single‐logic systems to more sophisticated multidevice, multilogic, and reconfigurable OELGs is comprehensively explored. Key advancements include the development of materials and device structures enabling multifunctional logic operations and the incorporation of in‐memory functionalities, critical for applications in high‐performance computing and real‐time data processing. This review also addresses the challenges that need to be overcome, such as stability, durability, integration with existing semiconductor technologies, and efficiency. By summarizing current research and proposing future directions, this review aims to guide the ongoing development of next‐generation optoelectronic architectures, poised to redefine the landscape of optical computing, communication, and data processing.